KINETIKA DELIGNIFIKASI SABUT KELAPA DENGAN PROSES PEROKSIDA ALKALI PADA PEMBUATAN PULP - Chadijah, Sitti (Teknosains, 2011)
Research has been conducted to find out the percentation of lignin in delignification process, rate of delignification, and order or reaction from the coconut fiber with peroxide alkali. Three experiments were done in this study : 1) optimalized of pH to find out highest lignin percentation from black liquor; 2) simple characterized of lignin by spectrophotometer IR; and 3) graphical interpretation of the percentation of lignin with cooking time to find out the order of reaction of delignification. The lignins were isolated by acid process. The obtained of lignin precipitation was filtrated, washed and rinsed with water until free from acid, and then heated at 105oC for 1 hours. The cooking time were varied as: 1 hour, 1,5 hours, 2 hours, 2,5 hours, 3 hours, 3,5 hours and 4 hours. The result of the experiments indicated that the highest lignin percentation were gotten in pH = 2, and from the IR spectra of lignin after was compared with standard lignin spectra, it can be seen that this sample is realy lignin. Than, according to graphical interpretation indicated that the order of reaction from coconut fiber delignification by peroxide alkali process followed first order. Key words : Black liquor, Delignification, peroxide alkali.